SEJARAH TARI JEPIN LEMBUT DI DESA SEKURA KECAMATAN TELUK KERAMAT KABUPATEN SAMBAS - Halim, Idris; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this research is the researcher's interest in Malay dance art especially the history of Jepin Lembut dance village   of Teluk Keramat Sekura Sambas district. The goal is to find out the history of dance Jepin Lembut by documenting the form of writing supported by photographs associated with a Jepin Lembut Dance. So the history of Jepin Lembtu dance can be known by the wider community.The method used is historical method, with qualitative research form. The approach in this research is interdisciplinary approach with the history as disciplines of sciences. Sources of data in this study are some of speakers who know the history of the existence of Jepin Lembt dance and documents the writing of scientific papers on dance Jepin Lembut. Data collection techniques in this study are observation, interview and documentation study. Techniques test the validity of data using source triangulation and extension of observation.The history of Jepin Lembut dance in the village   of Teluk Keramat Sekura Sambas district since 1950s, created by an artist named Abdullah. This dance arise in Tri Mandayan village. Firstly this dance showed in the marriage party as a society entertainment. Jepin Lembut dance in the village   of Teluk Keramat Sekura district have a glorious and decrease experience periods in the development era. Jepin Lembut dance was got a change at the presentation form elements.Keywords: Developmen, History, Jepin Lembut